2008
DOI: 10.1557/jmr.2008.0312
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical properties of indium tin oxide thin films with tilted and spiral microstructures prepared by oblique angle deposition

Abstract: The optical and electrical properties of “tilted” and “spiral” indium tin oxide (ITO) thin films are reported. The influence of the flux incident angle on the optical and electrical properties is investigated. When the flux incident angle is increased, both the refractive index and extinction coefficient of the film are decreased, but the resistivity is increased. Thus, the physical properties of the film can be modified over a wide range by adjusting the flux incident angle and substrate rotation scheme. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The fabrication of highly porous and/or sculptured ITO thin films has been attempted by e-beam OAD from ITO pellets, both under high vacuum conditions [316][317][318][319][320][321][322][323][324][325][326][327] and in a carrier gas flux (usually nitrogen) [320,[328][329][330]. Fig.…”
Section: Transparent Conductive Oxidesmentioning
confidence: 99%
“…The fabrication of highly porous and/or sculptured ITO thin films has been attempted by e-beam OAD from ITO pellets, both under high vacuum conditions [316][317][318][319][320][321][322][323][324][325][326][327] and in a carrier gas flux (usually nitrogen) [320,[328][329][330]. Fig.…”
Section: Transparent Conductive Oxidesmentioning
confidence: 99%
“…Oblique angle deposition (OAD) is a convenient method to fabricate thin films with a variety of nanostructures and unique optical properties [12][13][14][15]. Recently, transparent conductive thin film prepared by OAD technique is confirmed to improve the optical, electrical and light emitting properties of liquid crystal display (LCD) and light emitting diode (LED), which shows greatly potential application in photoelectrical field [16][17][18]. However, to our best knowledge, as one of important transparent conductive thin films, the research on ATO thin films prepared by OAD technique has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2(a), therefore, the n and k values of the TiO 2 film deposited at θ α = 80° are lower than those of TiO 2 film at θ α = 0° due to the increase of porosity within the film. The porosity within the film can be calculated by a well-known Bruggeman effective medium approximation [12]. The porosity of the TiO 2 film deposited at θ α = 80° was estimated to be approximately 55% from the parameters, i.e., n low = 1.438 and n high = 2.053 at λ = 540 nm.…”
Section: Methodsmentioning
confidence: 99%